ROAD TO INDONESIA ASEAN CHAIRMANSHIP 2023: INDONESIA FOREIGN POLICY PATTERN IN ASEAN - Farid Ramadhony; Yasef Firmansyah (Moestopo International Review on Social, Humanities, and Sciences, 2022)
After Indonesia became the chairperson of the G20 forum in 2022, Indonesia took another turn as chairman of the ASEAN forum in 2023. This momentum is necessary since 2023 is a political year in Indonesia, where Jokowi will enter the edge of his term in 2024. This research aims to identifying the low hanging fruits, in the context of Indonesia Chairmanship in ASEAN 2023, Rational Choice Theory will be used to answer the policy outcome that Indonesia used to influence national interest through the ASEAN. The vital Indonesian position of ASEAN might be divided into four phases. The first was during the founding of ASEAN itself, which resulted from the Bangkok declaration in 1967, and Indonesia's first chairmanship of ASEAN in 1976. The second was in 2003 when Indonesia had just shifted to democracy, the third was when Indonesia finally became a fully adopted democracy in 2011. Finally, In the current situation, many scholars believe ASEAN is at its lowest point in the last decade. Indonesia may use this momentum to restore ASEAN's position to become a regional organization that is considered not only in Asia but also at the global level, as mentioned in Bali Concord. This article aims primarily to identify the pattern of Indonesia's foreign policy through ASEAN and give suggestions for the foreign policy that may be in line with Indonesia's current national interest and leave legacy marks for Jokowi during Indonesia's Chairmanship of ASEAN. The result is Indonesia should Acknowledge the Myanmar Crisis, to secure its 2023 Chairmanship in ASEAN which will impact to 2024 General Elections.